FICTION - PHILOSOPHY OF LIFE (Archive of Conferences, 2021)
In this article, the poetry of our grandmothers in dangerous times, including Nodira, Anbar Otin, Khojanazar Huvaydo, Uvaysi's activity, Odil Yakubov, Utkir Hoshimov, Olmas Umarbekov, Abdulla Aripov, Muhammad Yusuf, Oybek, Hamid Olimjon, Said Ahmad, Abdulla Qahhor, Pirimqul Qodirov, Uncle Murod.